Determinación de la respuesta de dos enraizantes aplicados sobre la semilla de arroz (Oriza sativa) de la variedad INIAP-14, bajo condiciones de riego en la zona de Febres Cordero - Los Ríos - Lara Serrano, Wilson Roboan (2014)
This trial was conducted in the area of Mata de Cacao, Febres Cordero Parish, Canton Babahoyo, and Los Rios Province in the rice variety 'INIAP 14', planted under irrigation, testing organic products Rooting Green and Eco Master Hormones. Experimental design "randomized complete blocks" (DBCA) in three replications. The treatments were constituted by different doses Rooting and Green Master at 0.5 and 1.0l / ha; Eco Hormones in doses of 0.25 and 0.50l / ha; further treatment without rooting and absolute control (unfertilized without rooting) was included, giving a total of eight treatments. The results show that The Eco Rooting Hormones 0.5l / ha and Green Master 1.0l / ha, managed roots longest at 21 days after planting with 12.03 and 11.37cm, in that order; and also, the best dry roots. The treatment (T4) Eco Hormones 0.5l / ha, recorded the highest weight of leaf area at 21 days after sowing. The treatments (T2) Green Master 1.0l / ha and (T4) Eco Hormones 0.5l / ha, obtained the highest number of leaves per plant with values 11.67 and 12.33 in order, surpassing in 29.67% and 37% to control without rooting respectively. Treatment (T4) hormone Eco 0.5l / has reached the greatest number of panicles 347.33, exceeding 26.15% in the control without rooting. The treatment (T2) Green Master 1.0l / ha provided panicles with 126.67 grams and 1000 grams weight, exceeding 17.34% and 17.99% in control without rooting. The treatments (T2) Green Master 1.0l / ha and (T4) Eco Hormones 0.5l / ha, obtained the highest grain yields 8176 and 7954kg / ha, respectively. The treatment (T5) Control without rooting and unfertilized reached the lowest grain yield of 2636.67 kg / ha, giving an economic loss of $ 130.73 per hectare. The treatments (T2) Green xxii Master 1.0l / ha and (T4) Eco Hormones 0.5l / ha, achieved the highest economic profit of $ 951.80 and $ 885.36 per hectare, in that order.